Seed to seed mechanization in major oilseed crops - A review: Seed to seed mechanization in major oilseed crops - A review - A V RAMANJANEYULU,; P RAJAIAH, (Journal of Oilseeds Research, 2023)
Mechanization in oilseed crops help in efficient utilization of time, labour, fertilizers, water and timely completion of agronomic operations, reduce drudgery and wastage thus augment production efficiency. However, mechanization index (MI) in oilseed crops is low i.e. 32.52% for rapeseed and mustard, 26.4% for soybean, 11.83% for groundnut as compared to that of wheat (40.77%). As better crop yield are recorded in states with higher MI, efforts must be to design and develop cost effective machinery from seed to seed mechanization and also oil extraction in oilseeds crops in all the states.